(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
This study aimed to empirically examine whether rapid changes in the technological environment affect inter-organisational relationships. In the automotive industry, the advantage of cohesive and vertically integrated inter-organisational relationships has been pointed out conventionally. The development of connected cars, which can communicate bidirectionally with other systems outside the car, is eliciting significant changes in the traditional automotive products and the industry structure — changes generally associated with the automotive product structure moving closer to IT products. The aim was to empirically clarify what kind of network structure of inter-organisational relations firms are growing with changes in industrial structure by creating a database of actual firm behavior. The database was analyzed using the social network analysis method, and the characteristics of growing firms’ organisational network structure were extracted. Besides the traditional integrated inter-organisational relationships, the results show that there is a mixture of inter-organisational relationships with different characteristics of growth firms.